2014
DOI: 10.1146/annurev-physchem-040513-103649
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ligands in Determining the Exciton Relaxation Dynamics in Semiconductor Quantum Dots

Abstract: This article reviews the mechanisms through which molecules adsorbed to the surfaces of semiconductor nanocrystals, quantum dots (QDs), influence the pathways for and dynamics of intra- and interband exciton relaxation in these nanostructures. In many cases, the surface chemistry of the QDs determines the competition between Auger relaxation and electronic-to-vibrational energy transfer in the intraband cooling of hot carriers, and between electron or hole-trapping processes and radiative recombination in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
286
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(300 citation statements)
references
References 138 publications
(204 reference statements)
12
286
2
Order By: Relevance
“…[ 100 ] In addition, it was also shown that ultrafast electron relaxation can take place through Auger cooling, where the excess energy is transferred to the hole. [ 101 ] State-to-state relaxation can be measured in 2DES with the growth of cross peaks at high excitation and low detection energies corresponding to the optical transitions of interest.…”
Section: State-to-state Relaxationmentioning
confidence: 99%
“…[ 100 ] In addition, it was also shown that ultrafast electron relaxation can take place through Auger cooling, where the excess energy is transferred to the hole. [ 101 ] State-to-state relaxation can be measured in 2DES with the growth of cross peaks at high excitation and low detection energies corresponding to the optical transitions of interest.…”
Section: State-to-state Relaxationmentioning
confidence: 99%
“…[1][2][3][4][5][6] Given the NC composition, there are two important structural parameters -size ("quantum confinement effect") and the surface ligand chemistry of NCs -that control light absorption, enhance photogenerated charge separation, and reduce charge recombination, which together determine the catalytic efficiency. [7][8][9][10][11][12][13][14] Anatase TiO 2 is considered to be the most efficient and environmentally friendly photocatalyst. 15 However, its large band gap (~3.4 eV) allows only ultraviolet light absorption, which hinders its potential photocatalytic applications and commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, thiolates have been classified as electron donor ligands with hole trapping properties [28]. A study on carrier dynamics of QDs has shown that surface bound thiolates can affect the optical properties of QDs by trapping photogenerated holes on the surface of QDs.…”
Section: Page 8 Of 27mentioning
confidence: 99%